Pemanfaatan Tandan Kosong Sawit dan Lumpur IPAL Produksi Minyak Sawit Sebagai Bahan Baku Pembuatan Briket Dengan Crude Gliserol Sebagai Perekat - Adi Putra Pratama; Elvi Yenie; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Empty fruit bunch and WWTP mud palm oil production is a source biomass energy which has not been utilized optimally yet. This study aims determine the effect of differences in the compotition of raw materials and the addition of crude glycerol adhesive to the quality of briquettes produced using the carbonization process. The proses of making briquettes in this study with variying variations in the composition of raw material for empty fruit bunch : WWTP mud palm oil production 90%:10%, 80%:20%, 70%:30%, 60%:40% and crude glycerol adhesive concentration 0%, 5%, 10%, 15% from the total weight of 10 gram briquettes. The fixed variatons used are empty fruit bunch temperature of 450oC for 90 minutes, sludge temperature 300oC for 60 minutes, particle size used were less than 100 mesh and pressing preasure 100 bar. Drying is carried out indoors for 24 hours and then oven for 1 hour with temperature 105oC. the result showed that the best briquettes were in the composition of 90%:10% empty fruit bunch and WWTP mud palm oil production with the addition of 10% crude glycerol adhesive in which caloric value of 5244,83 cal/gr and compressive strength of 4,82 kg/cm2. Keywords: Empty fruit bunch, WWTP mud palm oil production, briquettes, caloric value, compressive strength.